European conformation and fat scores have no relationship with eating quality. (12th January 2016) - Bonny, S. P. F.; Pethick, D. W.; Legrand, I.; Wierzbicki, J.; Allen, P.; Farmer, L. J.; Polkinghorne, R. J.; Hocquette, J.-F.; Gardner, G. E.
Abstract : European conformation and fat grades are a major factor determining carcass value throughout Europe. The relationships between these scores and sensory scores were investigated. A total of 3786 French, Polish and Irish consumers evaluated steaks, grilled to a medium doneness, according to protocols of the 'Meat Standards Australia' system, from 18 muscles representing 455 local, commercial cattle from commercial abattoirs. A mixed linear effects model was used for the analysis. There was a negative relationship between juiciness and European conformation score. For the other sensory scores, a maximum of three muscles out of a possible 18 demonstrated negative effects of conformation score on sensory scores. There was a positive effect of European fat score on three individual muscles. However, this was accounted for by marbling score. Thus, while the European carcass classification system may indicate yield, it has no consistent relationship with sensory scores at a carcass level that is suitable for use in a commercial system. The industry should consider using an additional system related to eating quality to aid in the determination of the monetary value of carcasses, rewarding eating quality in addition to yield.